Education Of Health Protocol Implementation In The New Normal Era To The Elderly - Aniek Puspitosari (Jurnal Empathy Pengabdian Kepada Masyarakat, 2022)
Background: The community and the elderly, in particular, are expected to apply health protocols in the new average era to prevent the transmission of COVID-19. One of the efforts to prevent the transmission of Covid-19 in the elderly is to take promotive and preventive steps, including providing education to the elderly. Methods: The method of implementing community service activities with lectures and questions and answers about health protocols and efforts for healthy elderly, doing physical activity in the form of yoga relaxation exercises, and providing healthy supplementary food for the elderly. The counseling participants were elderly in RW 8, Kebakkalang, Kemiri Village, Kebakkramat District. Results: Counseling activities were carried out during September 2021 with 19 elderly participants. Participants can demonstrate directly the health protocols, such as steps to use hand sanitizer and washing hands. Participants also carry out yoga relaxation exercises for 30 minutes by keeping a distance between the elderly from one another. Conclusion: The results of this community service activity are expected to increase the knowledge of the elderly about preventing the occurrence of Covid-19 infection. The elderly can apply health protocols in every daily activity, improve physical fitness and become healthy and happy elderly.